The analysis of ground vibrations induced by foundation excavation test blasts nearby a buried high pressure gas pipeline - Dağaşan, Yasin; Erten, Oktay; Bilgin, H. (2015)
Due to the increase in earthwork rate in engineering applications, rock breakage nearby sensitive structures has become an important operation. Blasting, as one of the rock breakage methods, is a powerful tool and frequently used in mining and civil engineering works. Intensity of the ground vibrations induced by blasting is vital and should be controlled so as not to damage any property within the zone affected by blasting. In this case study, a controlled test blasting practice implemented nearby a buried high pressure gas pipeline is presented. Within the scope of this study, a number of test blasts were designed and carried out to identify the attenuation characteristics of the ground vibrations propagating through the pipeline direction. The empirical relations between the peak particle velocity and the scaled distance were established through a linear regression with a reasonable correlation coefficient. The vibration values measured during the test blasts were assessed according to the existing vibration regulations set for the blasting activities conducted nearby pipelines and the production blasts were then designed based on the site constants determined.